Corporate Libertarianism as one of the Major Sources of the Current Economic Crisis - Księżyk, Marianna (Managerial Economics, 2012)
The aim of this paper is to justify the thesis that the doctrine of corporate libertarianism defining, in the contemporary neoliberal capitalism, the participant behavior rules of participants in economic processes, providing corporations with privileges and the right to use their economic might, is an important source of the current crisis. To justify this thesis, the article discusses the sources of corporate libertarianism and its characteristics, the idea of corporate social responsibility and its realization in practice, and justifies the necessity of creating a new corporate mandate to ensure democratic control over corporations.